Social distancing and strengthened research community efforts to fight pandemics: producing a low-cost SARS-COV-2 ANTIGEN - Arbeitman, Claudia R. (2020)
At the beginning of the worldwide known SARS-CoV-2 pandemic, we have designed a strong collaborative working flow among researchers of different institutes in Argentina, taking advantage of each member's expertise. This effective working network allowed us to accelerate research and developments in a synergistic way. Our goals were to obtain antigens (proteins and multiprotein complexes) useful for the diagnosis and therapy against COVID19 and to make these developments available to society in the fastest and most cost-accessible possible fashion. In this scenario, we will present the advances regarding the scalable production of the receptor-binding domain (RBD) of the Spike protein of SARS-CoV-2. Also, we will present the improvements in the design of an antigen with better immunogenic characteristics compared with those of wild-type monomeric RBD, obtained through the covalent coupling of RBD with other proteins. Our efforts opened a big window of new and promising collaborative arms with other groups outside of our consortium: the purified proteins were useful for antiSARS-CoV-2 antibody detection, IgY production, camelid immunization for nanobody selection, vaccine investigations, and monoclonal antibody developments. We are confident not only that we will be able to positively contribute to the pandemic solution’s opportunities, but that the collaborative way among institutions –often underexploited– we chose to achieve to help fight pandemics will remain after the emergency is gone.